Chapter 10

SUCCESSIVE DIFFERENTIATION
OBJECTIVES
After going through this chapter you will be able to:
• find the higher order derivatives of a given function.
• know about Lebnitz theorem.
• know how to use Lebnitz theorem to find n
th
derivatives of a given function.
10.1 Introduction
We know that the derivative of a function y = f(x) with respect to (w.r.t.) is denoted
by either
dy
dx
or y
1
or f

(x). We shall be using the second notation i.e. y
1
often in this
unit. We also know that the first order derivative comes from the physical concept like
velocity of a moving particle and also by geometrical notion of tangent to a curve at a point.
Similarly, the second and higher order derivatives also come from the physical concepts of
acceleration and the curvatire of a curve etc. Let us now learn how to find the higher order
derivatives of a given function.
1
2
10.2 Higher Order Derivatives
The meaning of n
th
order derivative of a function is that we differentiate the given
function n successive times. Let us see some standard examples now:
Example 1. y = e
ax+b
Solution: Differentiating w.r.t. x successively we have,
y
1
= a.e
ax+b
y
2
= a.a.e
ax+b
= a
2
e
ax+b
y
3
= a
3
.e
ax+b
and hence on repeating this step n times we get,
y
n
= a
n
.e
ax+b
(10.1)
Example 2. y = a
mx
Solution: Differentiating w.r.t. x successively we have,
y
1
= a
mx
log a ×m = m.a
mx
log a,
y
2
= m.a
mx
(log a)
2
×m = m
2
.a
mx
(log a)
2
.
Thus, the n
th
derivative is:
y
n
= m
n
a
mx
(log a)
n
(10.2)
Example 3. y = (ax + b)
m
Solution: Differentiating w.r.t. x successively we have,
y
1
= m.(ax + b)
m−1
.a
y
2
= m.(m−1).(ax + b)
m−1−1
.a.a = m(m−1)(ax + b)
m−2
.a
2
y
3
= m(m−1)(m−2)(ax + b)
m−3
.a
3
Thus, on successive differentiation, the n
th
derivative is:
y
n
= m(m−1)(m−2) . . . (m−n + 1)(ax + b)
m−n
.a
n
(10.3)
3
Remark 1. Note that in the above formula m ≤ n or else the n
th
derivative y
n
would
become zero. For example, if y = (ax + b)
2
then using the above calculations we get:
y
3
= 2.1.0.(ax + b)
−1
.a
3
= 0.
Example 4. y =
1
ax + b
Solution: Given y =
1
ax + b
= (ax + b)
−1
Replacing m with −1 in the equation 10.3 we get
y
n
= (−1).(−2).(−3) . . . .(−1 −n + 1)).(ax + b)
−1−n
.a
n
i.e. (−1).(−2).(−3) . . . .(−n).a
n
.
1
(ax + b)
n+1
Thus, the n
th
derivative of y =
1
ax + b
is:
y
n
=
(−1)
n
.a
n
.n!
(ax + b)
n+1
(10.4)
Example 5. y =
1
(ax + b)
m
= (ax + b)
−m
Solution: Again using the equation 10.3 and substituting m with −m, we get
y
n
= (−m)(−m−1)(−m−2) . . . (−m−n + 1)(ax + b)
−m−n
.a
n
y
n
= (−1)
n
.(m)(m + 1)(m + 2) . . . (m + n −1)
a
n
(ax + b)
m+n
(10.5)
Example 6. y = log(ax + b)
Solution: Differentiating w.r.t. x successively we have,
y
1
=
1
ax + b
×a =
a
ax + b
y
2
=
a
2
.(−1)
(ax + b)
2
y
2
=
a
2
.(−1)(−2)
(ax + b)
3
Thus, on successive differentiation, the n
th
derivative is:
y
n
=
a
n
(−1)(−2) . . . (−(n −1))
(ax + b)
n
∴ y
n
=
a
n
(−1)
n−1
(ax + b)
n
×(n −1)! (10.6)
4
Example 7. y = sin(ax + b)
Solution: Differentiating w.r.t. x successively we have,
y
1
= a. cos(ax + b) = a. sin
_
(ax + b) +
π
2
_
y
2
= −a
2
sin(ax + b) = a
2
sin
_
(ax + b) + 2
π
2
_
Thus, on successive differentiation, the n
th
derivative is:
y
n
= a
n
sin
_
(ax + b) +

2
_
∴ y
n
= a
n
sin
_
(ax + b) +

2
_
(10.7)
Similarly, for y = cos(ax + b) we have
∴ y
n
= a
n
cos
_
(ax + b) +

2
_
(10.8)
Example 8. y = e
ax
sin(bx + c)
Solution: Differentiating w.r.t. x successively we have,
y
1
= e
ax
[a sin(bx + c) + b cos(bx + c)]
Let a = r cos α, b = r sin α ⇒r =

a
2
+ b
2
, α = tan
−1
_
b
a
_
∴ y
1
= e
ax
[r cos αsin(bx + c) + r sin αcos(bx + c)] = re
ax
sin(bx + c + α).
Similarly, we can show that y
2
= r
2
e
ax
sin(bx + c + 2α)
Thus, on successive differentiation, the n
th
derivative is:
y
n
= r
n
e
ax
sin(bx + c + nα)
∴ y
n
= (a
2
+ b
2
)
n/2
e
ax
sin
_
bx + c + ntan
−1
_
b
a
__
(10.9)
Similarly for y = e
ax
cos(bx + c) we have
∴ y
n
= (a
2
+ b
2
)
n/2
e
ax
cos
_
bx + c + ntan
−1
_
b
a
__
(10.10)
10.3 Leibnitz Theorem and its applications
5
We state now the Leibnitz theorem (without proof) for n
th
order derivative of product
of two n times differentiable fuctions. Let u, v be n times differentiable functions of x and
y = u.v then the n
th
derivative of y is given by :
y
n
= u
n
.v + n.u
n−1
v
1
+
n(n −1)
2
u
n−2
v
2
+ . . . + u.v
n
(10.11)
Note:
• To solve problems using Leibnitz theorem, we should take u as that function whose
n
th
derivative is known to us directly and v as that function whose higher order
derivatives are zero, for e.g. functions like x
3
, x
2
, have higher order derivatives zero.
• In some problems we need to use the first order derivative along with the function
recursively and then apply Leibnitz theorem to solve the problem.
Now let us solve some problems based on the formulae we have seen in Section 10.2 and
10.3.
Example 9. Find the n
th
derivative of sin
3
x.
Solution: Let y = sin
3
x
∵ sin 3x = 3 sin x −4 sin
3
x ⇒sin
3
x = (3 sin x −sin 3x)/4
∴ y =
1
4
[3 sin x −sin 3x]
Using eq (10.7) we have:
y
n
=
1
4
_
3 sin
_
x +

2
_
−3
n
sin
_
3x +

2
__
Example 10. Find the n
th
derivative of cos 2x cos 3x.
Solution: Let y = cos 2x cos 3x
∵ cos a cos b =
1
2
(cos(a + b) + cos(a −b)), we have y =
1
2
[cos 5x + cos x]
∴ using eq. (10.8), we get
y
n
=
1
2
_
5
n
cos
_
5x +

2
_
+ cos
_
x +

2
__
Example 11. Find the n
th
derivative of e
2x
cos 2x cos 3x.
6
Solution: Let y = e
2x
cos 2x cos 3x
Using the formula cos a cos b =
1
2
(cos(a + b) + cos(a −b)) and the eq. (10.10) we have;
y =
1
2
e
2x
(cos 5x + cos x)
∴ y =
1
2
_
e
2x
cos 5x + e
2x
cos x
_
∴ y
n
=
1
2
e
2x
_
(29)
n/2
cos
_
5x + ntan
−1
_
5
2
__
+ (5)
n/2
cos
_
x + ntan
−1
_
1
2
___
.
Example 12. If y = sin px + cos px then show that y
n
= p
n
[1 + (−1)
n
sin 2px]
1/2
Solution: Let y = sin px + cos px
∴ using eq. (10.7) and (10.8) we have,
y
n
= p
n
_
sin
_
px +

2
_
) + cos
_
px +

2
__
∴ y
n
= p
n
_
_
sin
_
px +

2
_
+ cos
_
px +

2
__
2
_
1/2
= p
n
_
1 + 2 sin
_
px +

2
_
cos
_
px +

2
__
1/2
= p
n
[1 + sin(2px + nπ)]
1/2
∴ y
n
= p
n
[1 + (−1)
n
sin 2px]
1/2
.
Hence proved.
Example 13. Find the n
th
derivative of y =
1
x
2
+ a
2
Solution: We have y =
1
(x −ia)(x + ia)
By using partial fractions, we get, y =
1
2ai(x −ia)

1
2ai(x + ia)
Using eq. (10.4) we get,
y
n
=
(−1)
n
n!
2ai
_
1
(x −ia)
n+1

1
(x + ia)
n+1
_
Example 14. Find the n
th
derivative of tan
−1
x.
Solution: Let y = tan
−1
x
∴ y
1
=
1
x
2
+ 1
=
1
(x −i)(x + i)
=
1
2i
_
1
x −i

1
x + i
_
∴ y
n
=
1
2i
_
(−1)
n−1
(n −1)!
(x −i)
n

(−1)
n−1
(n −1)!
(x + i)
n
_
. . . using eq. (10.4)
∴ y
n
=
(−1)
n−1
(n −1)!
2i
_
1
(x −i)
n

1
(x + i)
n
_
7
Example 15. Find the n
th
derivative of cos
−1
_
x −x
−1
x + x
−1
_
.
Solution: Let y = cos
−1
_
x −x
−1
x + x
−1
_
= cos
−1
_
x
2
−1
x
2
+ 1
_
Let x = tan θ, then y = cos
−1
(−cos 2θ) = cos
−1
cos(π + 2θ)
∴ y = π + 2θ = π + 2 tan
−1
x
Using Example 14 we have,
y
n
=
1
i
_
(−1)
n−1
(n −1)!
(x −i)
n

(−1)
n−1
(n −1)!
(x + i)
n
_
Now we shall see some problems based on Leibnitz’s theorem:
Example 16. Find the n
th
derivative of x
2
e
x
Solution: Given y = x
2
e
x
, let u = e
x
, v = x
2
..
Using the formula in (10.11) and also from (10.1) we have,
y
n
= e
x
x
2
+ ne
x
(2x) +
n(n −1)
2
e
x
(2)
∴ y
n
= e
x
.x
2
+ 2nx.e
x
+ n(n −1)e
x
= e
x
(x
2
+ 2nx + n(n −1)).
Example 17. Find the n
th
derivative of x
2
e
x
cos x.
Solution: Given y = x
2
e
x
cos x, let u = e
x
cos x, v = x
2
.
Using the formula in (10.11) and also from (10.10) we have,
y
n
= x
2
_
2
n
2
e
x
cos
_
x +

4
__
+ n(2x)
_
2
n−1
2
e
x
cos
_
x +
(n −1)π
4
__
+
n(n −1)
2
.2.
_
2
n−2
2
e
x
cos
_
x +
(n −2)π
4
__
Example 18. If y = tan x then show that y
n
(0)−
n
C
2
y
n−2
(0)+
n
C
4
y
n−4
(0)+. . . = sin
_

2
_
.
Solution: Given y = tan x =
sin x
cos x
⇒(cos x)y = sin x.
Now using the formula in (10.11) and also from (10.7), (10.8), we have
cos x.y
n
(x) +
n
C
1
(−sin x)y
n−1
(x) +
n
C
2
(−cos x)y
n−2
(x) + . . . = sin
_
x +

2
_
By substituting x = 0 on both the sides, we get
y
n
(0) −
n
C
2
y
n−2
(0) +
n
C
4
y
n−4
(0) + . . . = sin
_

2
_
.
8
Example 19. If y =
log x
x
then show that y
n
=
(−1)
n
.n!
x
n+1
_
log x −
_
1 +
1
2
+
1
3
+ . . . +
1
n
__
Solution: Let u = log x, v =
1
x
.
From (10.6) and from (10.4), we have, u
n
=
(−1)
n−1
.(n −1)!
x
n
, v
n
=
(−1)
n
.n!
x
n+1
Now ∵ y = uv, using (10.11), we get,
y
n
= u.v
n
+ n.u
1
.v
n−1
+
n(n −1)
2
u
2
.v
n−2
+ . . . + u
n
.v
∴ y
n
= log x.
(−1)
n
.n!
x
n+1
+ n.
1
x
(−1)
n−1
.(n −1)!
x
n
+
n(n −1)
2
_
−1
x
2
_
(−1)
n−2
.(n −2)!
x
n−1
+
n(n −1)(n −2)
6
_
2
x
3
_
(−1)
n−3
.(n −3)!
x
n−2
+ . . . +
(−1)
n−1
.(n −1)!
x
n
1
x
= log x.
(−1)
n
.n!
x
n+1

(−1)
n
.n!
x
n+1

(−1)
n
.n!
x
n+1
1
2

(−1)
n
.n!
x
n+1
1
3
. . . −
(−1)
n
.n!
x
n+1
1
n
∴ y
n
=
(−1)
n
.n!
x
n+1
_
log x −
_
1 +
1
2
+
1
3
+ . . . +
1
n
__
Example 20. If y =
sin
−1
x

1 −x
2
then show that (1−x
2
)y
n+2
−(2n+3)x.y
n+1
−(n+1)
2
y
n
= 0
Solution: We have y =
sin
−1
x

1 −x
2


1 −x
2
.y = sin
−1
x
Differentiating w.r.t.

x

we have,

1 −x
2
.y
1
+
−2x
2

1 −x
2
.y =
1

1 −x
2
∴ (1 −x
2
).y
1
−x.y = 1
Differentiating again w.r.t.

x

, we get,
(1 −x
2
)y
2
−2.x.y
1
−x.y
1
−y = 0
∴ (1 −x
2
)y
2
−3.x.y
1
−y = 0.
Now we apply Leibnits formula (10.11) to each term above, to get,
_
(1 −x
2
)y
n+2
+ n.(−2x)y
n+1
+
n(n + 1)
2
.(−2).y
n
_
−3[x.y
n+1
+ n.1.y
n
] −y
n
= 0
∴ (1 −x
2
)y
n+2
−(2n + 3)x.y
n+1
−(n + 1)
2
y
n
= 0
10.4 Let Us Sum Up
9
In this chapter we have seen how to do successive differentiation of functions like
e
mx
, a
mx
, sin(ax + b), cos(ax + b), log(ax + b), e
ax
sin(bx + c) . . . etc. Also we have seen
how Leibnitz theorem is used to find the n
th
derivative of product of two functions.
10.5 Unit End Exercise
1. Find the n
th
derivative of the following:
(a)
x
(x −1)(x −3)
(b)
x
(x −1)(x −2)(x −3)
(c) x
2
.e
2x
(d) x
3
.e
2x
(e) tan
−1
x
(f) sin(3x + 2)
(g) e
2x
sin(3x + 4)
(h) e
2x
sin x cos
2
x
2. If x = e
y
then show that (1 −y).y
2
= (2 −y).(y
1
)
2

a = m(m − 1)(ax + b)m−2 . x successively we have. x successively we have. x successively we have.t.r. y = eax+b Solution: Differentiating w. (m − n + 1)(ax + b)m−n .(m − 1).eax+b and hence on repeating this step n times we get.eax+b y2 = a.a2 y3 = m(m − 1)(m − 2)(ax + b)m−3 . y = amx Solution: Differentiating w. the nth derivative is: yn = mn amx (log a)n Example 3.t. yn = an . the nth derivative is: yn = m(m − 1)(m − 2) .(ax + b)m−1−1 .(ax + b)m−1 . y1 = a.a3 Thus. Thus.1) .eax+b = a2 eax+b y3 = a3 . y1 = amx log a × m = m.2 10. . . y2 = m.a y2 = m.a.2 Higher Order Derivatives The meaning of nth order derivative of a function is that we differentiate the given function n successive times.an (10.3) (10.amx log a.amx (log a)2 × m = m2 . y = (ax + b)m Solution: Differentiating w. Let us see some standard examples now: Example 1.amx (log a)2 .a.2) (10.r. on successive differentiation.t.eax+b Example 2.r. y1 = m.

.(−2). . (−m − n + 1)(ax + b)−m−n .6) an (ax + b)m+n (10. .(−1)(−2) y2 = (ax + b)3 Thus. y = (−1)n . the nth derivative of y = ax + b yn = Example 5.4) 1 = (ax + b)−m (ax + b)m Solution: Again using the equation 10. (−1).(−2).3 and substituting m with −m.(−3) .3 Remark 1.e. . For example.1.(−1) y2 = (ax + b)2 a2 .an .(−3) .t. . the nth derivative is: an (−1)(−2) . .(−n). . (ax + b)n+1 1 is: Thus.an 1 i.r. . if y = (ax + b)2 then using the above calculations we get: y3 = 2. x successively we have.n! (ax + b)n+1 (10.(−1 − n + 1)). .a3 = 0. Example 4. (m + n − 1) Example 6. y = log(ax + b) Solution: Differentiating w.(m)(m + 1)(m + 2) .an . (−(n − 1)) yn = (ax + b)n ∴ yn = an (−1)n−1 × (n − 1)! (ax + b)n (10. 1 a y1 = ×a= ax + b ax + b a2 . . . .3 we get Solution: Given y = yn = (−1).5) .(ax + b)−1 .an yn = (−1)n . on successive differentiation.0.(ax + b)−1−n . we get yn = (−m)(−m − 1)(−m − 2) . Note that in the above formula m ≤ n or else the nth derivative yn would become zero. y = 1 ax + b 1 = (ax + b)−1 ax + b Replacing m with −1 in the equation 10.

4 Example 7. y = sin(ax + b) Solution: Differentiating w. x successively we have. sin (ax + b) + 2 π y2 = −a2 sin(ax + b) = a2 sin (ax + b) + 2 2 th Thus.t.r. the n derivative is: nπ yn = an sin (ax + b) + 2 ∴ yn = an sin (ax + b) + Similarly. y = eax sin(bx + c) Solution: Differentiating w.8) nπ 2 (10. the nth derivative is: yn = rn eax sin(bx + c + nα) ∴ yn = (a2 + b2 )n/2 eax sin bx + c + n tan−1 Similarly for y = eax cos(bx + c) we have ∴ yn = (a2 + b2 )n/2 eax cos bx + c + n tan−1 b a (10. on successive differentiation.3 Leibnitz Theorem and its applications . on successive differentiation.r. y1 = eax [a sin(bx + c) + b cos(bx + c)] √ Let a = r cos α.7) b a ∴ y1 = eax [r cos α sin(bx + c) + r sin α cos(bx + c)] = reax sin(bx + c + α). we can show that y2 = r2 eax sin(bx + c + 2α) Thus.t. for y = cos(ax + b) we have ∴ yn = an cos (ax + b) + Example 8. cos(ax + b) = a. Similarly.10) b a (10. π y1 = a.9) 10. α = tan−1 nπ 2 (10. b = r sin α ⇒ r = a2 + b2 . x successively we have.

Solution: Let y = sin3 x sin 3x = 3 sin x − 4 sin3 x ⇒ sin3 x = (3 sin x − sin 3x)/4 1 ∴ y = [3 sin x − sin 3x] 4 Using eq (10. Find the nth derivative of cos 2x cos 3x. have higher order derivatives zero.5 We state now the Leibnitz theorem (without proof) for nth order derivative of product of two n times differentiable fuctions. functions like x3 .v + n. x2 .8).11) .3.g. . Find the nth derivative of sin3 x. .7) we have: 1 nπ nπ yn = 3 sin x + − 3n sin 3x + 4 2 2 Example 10.vn 2 (10.un−1 v1 + Note: • To solve problems using Leibnitz theorem. we get 1 n nπ nπ yn = 5 cos 5x + + cos x + 2 2 2 Example 11. • In some problems we need to use the first order derivative along with the function recursively and then apply Leibnitz theorem to solve the problem. Now let us solve some problems based on the formulae we have seen in Section 10. we have y = [cos 5x + cos x] 2 2 ∴ using eq. for e.v then the nth derivative of y is given by : yn = un . Let u. Find the nth derivative of e2x cos 2x cos 3x. n(n − 1) un−2 v2 + . Example 9.2 and 10. v be n times differentiable functions of x and y = u. Solution: Let y = cos 2x cos 3x 1 1 cos a cos b = (cos(a + b) + cos(a − b)). + u. we should take u as that function whose nth derivative is known to us directly and v as that function whose higher order derivatives are zero. (10.

4) we get. (−1)n n! 1 1 yn = − 2ai (x − ia)n+1 (x + ia)n+1 Example 14. .6 Solution: Let y = e2x cos 2x cos 3x 1 Using the formula cos a cos b = (cos(a + b) + cos(a − b)) and the eq. y = Using eq. we get.10) we have. (10. (10. Find the nth derivative of y = Solution: We have y = 1 (x − ia)(x + ia) 1 1 − 2ai(x − ia) 2ai(x + ia) 1 + a2 x2 By using partial fractions. . Example 13. 2 1 2x y = e (cos 5x + cos x) 2 1 2x ∴y= e cos 5x + e2x cos x 2 5 1 1 + (5)n/2 cos x + n tan−1 . (10. ∴ yn = e2x (29)n/2 cos 5x + n tan−1 2 2 2 Example 12. Hence proved. nπ nπ yn = pn sin px + ) + cos px + 2 2 1/2 nπ nπ 2 n ∴ yn = p sin px + + cos px + 2 2 nπ 1/2 nπ cos px + = pn [1 + sin(2px + nπ)]1/2 = pn 1 + 2 sin px + 2 2 ∴ yn = pn [1 + (−1)n sin 2px]1/2 . (10. using eq. Find the nth derivative of tan−1 x. If y = sin px + cos px then show that yn = pn [1 + (−1)n sin 2px]1/2 Solution: Let y = sin px + cos px ∴ using eq.8) we have. Solution: Let y = tan−1 x 1 1 1 1 1 ∴ y1 = 2 = = − x +1 (x − i)(x + i) 2i x − i x + i n−1 1 (−1) (n − 1)! (−1)n−1 (n − 1)! ∴ yn = − 2i (x − i)n (x + i)n n−1 (−1) (n − 1)! 1 1 − ∴ yn = 2i (x − i)n (x + i)n .7) and (10.4) .

let u = ex . x + x−1 x − x−1 x2 − 1 = cos−1 x + x−1 x2 + 1 −1 −1 Let x = tan θ.10) we have. If y = tan x then show that yn (0)−n C2 yn−2 (0)+n C4 yn−4 (0)+. . yn = x2 2 2 ex cos x + + n nπ 4 + n(2x) 2 n−1 2 ex cos x + (n − 1)π 4 n−2 n(n − 1) (n − 2)π .x2 + 2nx. v = x2 .yn (x) +n C1 (− sin x)yn−1 (x) +n C2 (− cos x)yn−2 (x) + . .8). cos x Now using the formula in (10. let u = ex cos x. Example 17. = sin sin x ⇒ (cos x)y = sin x. Using the formula in (10. 2 .11) and also from (10. . .11) and also from (10. Find the nth derivative of x2 ex Solution: Given y = x2 ex . Find the nth derivative of x2 ex cos x. Find the nth derivative of cos−1 Solution: Let y = cos−1 x − x−1 . 2 2 ex cos x + 2 4 Example 18. v = x2 . 2 Solution: Given y = tan x = nπ . . Solution: Given y = x2 ex cos x.1) we have.7). n(n − 1) x yn = ex x2 + nex (2x) + e (2) 2 ∴ yn = ex .ex + n(n − 1)ex = ex (x2 + 2nx + n(n − 1)).7 Example 15.. . Using the formula in (10.2.11) and also from (10. = sin . 1 (−1)n−1 (n − 1)! (−1)n−1 (n − 1)! yn = − i (x − i)n (x + i)n Now we shall see some problems based on Leibnitz’s theorem: Example 16. then y = cos (− cos 2θ) = cos cos(π + 2θ) ∴ y = π + 2θ = π + 2 tan−1 x Using Example 14 we have. = sin x + 2 By substituting x = 0 on both the sides. we have nπ cos x. we get nπ yn (0) −n C2 yn−2 (0) +n C4 yn−4 (0) + . (10.

r.n! 1 1 1 = log x − 1 + + + . we get. + xn+1 x xn 2 x2 xn−1 (−1)n−1 . . √ −2x 1 1 − x2 .y1 − x. we get. x Example 19.vn−1 + ∴ yn (−1)n−1 . . + un .x.. + x xn+1 2 3 n 1 .(n − 3)! + .t. + n+1 x 2 3 n sin−1 x √ then show that (1−x2 )yn+2 −(2n+3)x.6) and from (10.n! 1 (−1) .8 log x (−1)n . + + 6 x3 xn−2 xn x n n n n n (−1) .4). vn = xn xn+1 ∴ yn n(n − 1) u2 .4 Let Us Sum Up .n! .n! 1 1 1 then show that yn = log x − 1 + + + .(−2).vn−2 + .yn+1 − (n + 1)2 yn = 0 10.y = sin−1 x 1 − x2 Differentiating w. n+1 n+1 n+1 n+1 x x x 2 x 3 xn+1 n n (−1) . x . + n.yn ] − yn = 0 2 ∴ (1 − x2 )yn+2 − (2n + 3)x..n! 1 − − − .(n − 1)! 1 n(n − 1)(n − 2) 2 (−1)n−3 .(n − 1)! (−1)n . If y = Solution: Let u = log x. to get.u1 .. v = From (10.1.y = 1 Differentiating again w..y1 + √ .yn+1 + n.y = √ 2 1 − x2 1 − x2 2 ∴ (1 − x ). (1 − x2 )y2 − 2. un = Now y = uv.v 2 (−1)n .y1 − x. − = log x.(n − 1)! n(n − 1) −1 (−1)n−2 .yn − 3[x. . we have.x.n! (−1) . If y = 2 1−x √ sin−1 x Solution: We have y = √ ⇒ 1 − x2 .t.11) to each term above.r.n! 1 (−1) . x we have. Now we apply Leibnits formula (10.vn + n. .yn+1 −(n+1)2 yn = 0 Example 20. .n! 1 (−1)n−1 . using (10. yn = u.y1 − y = 0 ∴ (1 − x2 )y2 − 3.n! (−1) . n(n + 1) (1 − x2 )yn+2 + n. .y1 − y = 0.(n − 2)! = log x.11).(−2x)yn+1 + .

If x = ey then show that (1 − y).(y1 )2 . eax sin(bx + c) . Find the nth derivative of the following: x (x − 1)(x − 3) x (b) (x − 1)(x − 2)(x − 3) (a) (c) x2 . amx .e2x (e) tan−1 x (f) sin(3x + 2) (g) e2x sin(3x + 4) (h) e2x sin x cos2 x 2.5 Unit End Exercise 1. Also we have seen how Leibnitz theorem is used to find the nth derivative of product of two functions. etc.9 In this chapter we have seen how to do successive differentiation of functions like emx . . . sin(ax + b). cos(ax + b). 10.e2x (d) x3 . log(ax + b).y2 = (2 − y).